ERCP improves mortality in acute biliary pancreatitis without cholangitis - Novikov, Aleksey A.; Fieber, Jennifer H.; Saumoy, Monica; Rosenblatt, Russell; Mekelburg, Shirley A. Cohen; Shah, Shawn L.; Crawford, Carl V., Jr (Endoscopy International Open, 2021)
Background and study aims Acute pancreatitis (AP) is an increasingly common indication for hospitalization in the United States. The necessity for endoscopic retrograde cholangiopancreatography (ERCP) and the timing of ERCP in acute gallstone-related pancreatitis without cholangitis (AGPNC) is controversial. The aim of this study was to evaluate the association of ERCP and its performance during admission with mortality and length of stay (LOS) in patients with AGPNC.Patients and methods We queried the Nationwide Inpatient Sample (NIS) from 2004 to 2014 to identify all patients with admissions for gallstone AP. We excluded patients with chronic pancreatitis or concurrent cholangitis, and those who were transferred from elsewhere for treatment. Our primary outcome measure was inpatient mortality. Our secondary outcome measure was hospital length of stay (LOS).Results We identified 491,011 records eligible for analysis. Of the patients, 30.6 % (150,101) had AGPNC. There were 1.34 deaths per 100 admissions in patients with AGPNC. The average LOS was 5.88 (± 6.38) days with a median stay of 4 days (range, 3–7). When adjusted for age, Elixhauser Comorbidity Index, and severe pancreatitis, patients with ERCP during admission were 43 % less likely to die. ERCP performed between Days 3 and 9 of hospitalization resulted in a significant mortality benefit. Among those who had ERCP, a shorter wait time for ERCP was associated with a shorter LOS after adjustment for demographics and severity of illness.Conclusion ERCP performed during inpatient admission for AGPNC was associated with decreased mortality. These data support early ERCP in patients with acute gallstone pancreatitis without cholangitis.